Tafenoquine plus chloroquine for the treatment and relapse prevention of Plasmodium vivax malaria (DETECTIVE): A multicentre, double-blind, randomised, phase 2b dose-selection study - Alejandro Llanos-Cuentas (2018)
Background Clinical eff ectiveness of previous regimens to treat Plasmodium vivax infection have been hampered by compliance. We aimed to assess the dose-response, safety, and tolerability of single-dose tafenoquine plus 3-day chloroquine for P vivax malaria radical cure. Methods In this double-blind, randomised, dose-ranging phase 2b study, men and women (aged ≥16 years) with microscopically confi rmed P vivax monoinfection (parasite density >100 to <100 000 per μL blood) were enrolled from community health centres and hospitals across seven sites in Brazil, Peru, India, and Thailand. Patients with glucose- 6-phosphate dehydrogenase enzyme activity of less than 70% were excluded. Eligible patients received chloroquine (days 1-3) and were randomly assigned (1:1:1:1:1:1) by a computer-generated randomisation schedule to receive singledose tafenoquine 50 mg, 100 mg, 300 mg, or 600 mg, primaquine 15 mg for 14 days, or chloroquine alone. Randomisation was stratifi ed by baseline parasite count (≤7500 and >7500 per μL blood). The primary effi cacy endpoint was relapse-free effi cacy at 6 months from initial dose (ie, clearance of initial infection without subsequent microscopically confi rmed infection), analysed by intention to treat. This study is registered with ClinicalTrials.gov, number NCT01376167. Findings Between Sept 19, 2011, and March 25, 2013, 329 patients were randomly assigned to a treatment group (chloroquine plus tafenoquine 50 mg [n=55], 100 mg [n=57], 300 mg [n=57], 600 mg [n=56]; or to chloroquine plus primaquine [n=50]; or chloroquine alone [n=54]). Relapse-free effi cacy at 6 months was 57.7% (95% CI 43-70) with tafenoquine 50 mg, 54.1% (40-66) with tafenoquine 100 mg, 89.2% (77-95) with tafenoquine 300 mg, 91.9% (80-97) with tafenoquine 600 mg, 77.3% (63-87) with primaquine, and 37.5% (23-52) with chloroquine alone. Tafenoquine 300 mg and 600 mg had better effi cacy than chloroquine alone (treatment diff erences 51.7% [95% CI 35-69], p&0.0001, with tafenoquine 300 mg and 54.5% [38-71], p <0.0001, with tafenoquine 600 mg), as did primaquine (treatment diff erence 39.9% [21-59], p=0.0004). Adverse events were similar between treatments. 29 serious adverse events occurred in 26 (8%) of 329 patients; QT prolongation was the most common serious adverse event (11 [3%] of 329), occurring in fi ve (2%) of 225 patients receiving tafenoquine, four (8%) of 50 patients receiving primaquine, and two (4%) of 54 patients receiving chloroquine alone, with no evidence of an additional eff ect on QT of chloroquine plus tafenoquine coadministration. Interpretation Single-dose tafenoquine 300 mg coadministered with chloroquine for P vivax malaria relapse prevention was more effi cacious than chloroquine alone, with a similar safety profi le. As a result, it has been selected for further clinical assessment in phase 3. Funding GlaxoSmithKline, Medicines for Malaria Venture.